The role of psychosocial factors and treatment need in dental service use and oral health among adults in Norway - Jönsson, Birgitta; Holde, Gro Eirin; Baker, Sarah R. (Community Dentistry and Oral Epidemiology, 2020)
Objectives - This study aimed to explore whether population characteristics were associated with the use of dental services, individual's personal oral health practices, dental caries and oral health‐related impacts using the revised Andersen's behavioural model as the theoretical framework. Methods - This cross‐sectional study included participants from a Norwegian general population (N = 1840; 20‐79 years) included in the Tromstannen—Oral Health in Northern Norway (TOHNN) study. The variables included in the model were social structure (income, education, urbanization), sense of coherence (SOC), enabling resources (difficulties accessing the dentist, declined treatment, dental anxiety), treatment need, use of dental services, toothbrushing frequency, sugary soda drink consumption, decayed teeth and oral health‐related impacts (OHIP‐14). Structural equation modelling was used to test the direct and indirect effects within Andersen's behavioural model of access and health outcomes. Results - Andersen's behavioural model fit the data well and explained a large part of the variance in use of dental services (58%), oral health‐related impacts (48%) and, to a lesser extent, decayed teeth (12%). More social structures and a stronger SOC was associated with more enabling resources, which in turn, was associated with more use of dental services. Social structures were not directly associated with use of dental services or decayed teeth but were predictive of oral health‐related impacts. A stronger SOC was associated with more frequent toothbrushing, less soda drink consumptions, fewer decayed teeth and less oral health‐related impacts. Self‐perceived need did not predict dental attendance but was associated with decayed teeth. A less frequent use of dental services, less frequent toothbrushing and more frequent sugary soda drink consumption were associated with more decayed teeth. Decayed teeth were not associated with oral health‐related impacts. Conclusion - The findings suggests that, in addition to focusing on ...